The reduction in circulating levels of melatonin may be associated with the development of preeclampsia - Zeng, K; Gao, Y; Wan, J; Tong, M; Lee, A C; Zhao, M; Chen, Q (Journal of human hypertension, 2016)
Placental dysfunction and oxidative stress contribute to the pathogenesis of preeclampsia, which is a pregnancy-specific disorder. It has been suggested that the incidence of preeclampsia has a seasonal variation. Melatonin, as a seasonal factor, has been suggested to be involved in a successful pregnancy. In this study, we investigated the association of circulating levels of melatonin with preeclampsia. Serum was collected from women with preeclampsia ( n =113) and gestation-matched healthy pregnant women, and the levels of melatonin were measured. In addition, the expression of melatonin receptors was examined in preeclamptic placentae ( n =27). The association of the incidence of preeclampsia and seasonal variation was also analysed from 1491 women with preeclampsia within 77 745 healthy pregnancies. The serum levels of melatonin were significantly reduced in women with preeclampsia at presentation and these reduced serum levels of melatonin were not associated with the severity or time onset of preeclampsia nor with seasonal variation. The expression of melatonin receptor, MT1 was reduced in preeclamptic placentae. The incidence of preeclampsia was did exhibit seasonal variation, but this was largely due to the increase in the incidence of mild or late-onset preeclampsia. Our results demonstrate that reduced melatonin levels are associated with the development of preeclampsia but that the circulating levels of melatonin do not appear to be subject to seasonal variation during pregnancy.